2001
DOI: 10.1677/joe.0.1680153
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of endothelin-1 on the contractility of myometrium obtained from pre- and postmenopausal women

Abstract: This study was conducted to evaluate the responsiveness of human nonpregnant myometrium to endothelin 1 (ET1) (10 10 M-10 6 M) and KCl (80 mM) in relation to the hormonal profile of the women, who were allocated into three groups: group 1, premenopausal follicular phase, n=14, group 2, premenopausal luteal phase, n=20, and group 3, postmenopausal women, n=12. At a concentration of 10 6 M, ET1 in both groups 1 and 2 induced very low ripples of high frequency (group 1: 80 14%, n=5, group 2: 314 63%, n=11; P<0·05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
4
0
2
Order By: Relevance
“…Of note also, contractility although low, is maintained well into post-menopause. This is consistent with an earlier in vitro study which had found spontaneous activity in post-menopausal women (Domali et al 2001). These latter authors also demonstrated responsiveness to endothelin 1, which could be modified by ovarian steroids.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note also, contractility although low, is maintained well into post-menopause. This is consistent with an earlier in vitro study which had found spontaneous activity in post-menopausal women (Domali et al 2001). These latter authors also demonstrated responsiveness to endothelin 1, which could be modified by ovarian steroids.…”
Section: Discussionsupporting
confidence: 93%
“…One might assume that following the menopause, uterine activity ceases. However, rhythmical myometrial contractions have been seen by ultrasound examination in postmenopausal women (de Vries et al 1990) and one previous study has reported low levels of spontaneous activity in strips from human post-menopausal myometrium in vitro (Domali et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The amplitude of the spontaneous contractions was chosen because it expresses the contractile potential of each colonic strip. The change in basal tone was calculated using the formula: χ=β/α х 100 [19], where χ is the percentage change in the basal tone, α is the mean amplitude of the spontaneous colonic contractions, and β is the mean values of the distance of the lower parts of the induced contractions from the curve initial baseline.…”
Section: Change In Basal Tonementioning
confidence: 99%
“…Έτσι παρατηρείται µείωση της ανταπόκρισης του µυοµητρίου στην ωκυτοκίνης παρουσία οιστραδιόλης , όπως και µείωση της έντασης της ανταπόκρισης στη δράση της ΕΤ 1 παρουσία προγεστερόνης ωστόσο δεν έχουν διευκρινιστεί ακριβώς οι βιοχηµικές οδοί µέσω των οποίων πραγµατοποιούνται αυτές οι αλλαγές (Fu et al 1996, Phaneuf et al 1997,Fomin et al 1999, Domali et al 2001 Τα κριτήρια επιλογής των γυναικών για να συµπεριληφθούν στο πειραµατικό πρωτόκολλο ήταν:…”
Section: Nep -Neutral Endopeptidaseunclassified
“…Μελέτες που γίνανε σε µυοµήτριο προ και µετεµµηνοπαυσιακών γυναικών, έδειξαν ότι το ορµονικό προφίλ τροποποιεί τη συσταλτική ανταποκρισιµότητα του µυοµητρίου στη δράση της ΕΤ 1 (Domali et al 2001). Στην οµάδα της εµµηνόπαυσης η δράση της ΕΤ 1 είναι µεγαλύτερης διάρκειας και η προγεστερόνη έχει ανασταλτική δράση στην από την ΕΤ 1 προκαλούµενη συστολή.…”
Section: το εµβαδό της επιφάνειας κάτω από την καµπύληunclassified